Dermal bioaccessibility and absorption of polycyclic aromatic hydrocarbons (PAHs) in indoor dust and its implication in risk assessment. (September 2020) - Luo, Kesong; Zeng, Diya; Kang, Yuan; Lin, Xunyang; Sun, Na; Li, Cheng; Zhu, Mengqi; Chen, Zhenwen; Man, Yu Bon; Li, Hui
Abstract: Numerous studies have focused on assessing the risk of human exposure to polycyclic aromatic hydrocarbons (PAHs) in indoor dust via dermal contact. However, the dermal bioaccessibility and dermal absorption of PAHs in indoor dust have seldom been reported. In the present study, the effects of temperature, sweat ratio, solid-liquid ratio and incubation time on the dermal bioaccessibility of PAHs were examined. Naphthalene, phenanthrene, pyrene and benzo[a]pyrenewere selected for examination in an absorption assay with keratinocyte cells. The results showed the release of PAHs from indoor dust fitted a first-order one-compartment model. Naphthalene had the highest rate of release, which was consistent with the bioaccessibility assay results. In addition, the absorption rate of naphthalene and phenanthrene by keratinocytes was higher than that of pyrene and benzo[a]pyrene, with the latter being of higher molecular weight. These results indicated that low molecular weight PAHs were much more easily absorbed via dermal contact than were high molecular weight PAHs. The dermal bioavailability of PAHs in indoor dust was estimated by multiplying the bioaccessibility of PAHs in indoor dust by the ratio of dermal absorption by skin cells, and ranged from 0.12 to 51.0%. These data will be useful in risk assessments. Graphical abstract: Image 1 Highlights: The dermal bioaccessbility of PAHs is generally correlated with Kow . LMW PAHs are more easily absorbed via dermal contact than HMW PAHs. Dermal bioavailability of PAHs ranged from 0.12 to 51.0%. Abstract : The dermal bioavailability of PAHs ranging from 0.12 to 51.0% could be employed in risk assessment.